Parasarcophaga sachtlebeni Lehrer 1959 ein Synonym von Parasarcophaga jacobsoni Rohdendorf 1937 (Diptera: Sarcophagidae). - Povolný, Dalibor (Contributions to Entomology = Beiträge zur Entomologie, 1961)
There is demonstrated Parasarcophaga sachtlebeni, described in 1959 by Lehrer, largely corresponding as to its morphologic characters to Parasarcophaga jacobsoni Rohdendorf so that the former has to be regarded as a synonym of the latter. Nomenclatural Actssachtlebeni Lehrer, 1959 (Parasarcophaga), syn. n. of Parasarcophaga jacobsoni Rohdendorf, 1937